TUJUAN ADMINISTRASI NEGARA DALAM BIDANG PARTISIPASI SOSIAL: MEMBANGUN KESETARAAN, KEADILAN, DAN SOLIDARITAS MELALUI KEBIJAKAN PUBLIK YANG BERORIENTASI MASYARAKAT - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2025)
Public administration plays a crucial role in promoting social participation to create a fair, equitable, and solidarity-based society. Through public policies focused on community needs, the government strives to reduce social inequality while providing equal opportunities for all individuals, regardless of their economic, cultural, or social background. This approach aims to ensure the equitable distribution of resources, protect the fundamental rights of citizens, and strengthen mutual support among community members. Success in building inclusive social participation can support the creation of a sustainable and harmonious environment. By prioritising the principles of justice and equality, public policy not only aims to address inequality but also empowers communities to actively contribute to shared development. This results in a stronger sense of belonging among citizens, while also strengthening trust in the government. Overall, community-oriented state administration is key to creating a better life for all. Through fair policies and approaches that support broad social participation, the state can build a solid foundation for a more equitable, respectful, and solidarity-filled society.